Profile of effective teaching [videorecording]. Special education - Silver, Jon; Moir, Ellen; Moore, Sydnie; New Teacher Center (Santa Cruz, California) (New Teacher Center, 2005)
"Powerful integration of instructional strategies, classroom scenes include: inquiry and project-based learning, use of multicultural literature, physical movement embedded in lessons, integrating different learning modalities, SDAIE techniques, balance literacy program, infusing the arts throughout the curriculum, student centered learning environment."